COMPETITIVENESS OF THE LUZNAVA MANOR - Dembovska, Iveta; Litavniece, Lienīte; Silicka, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Customers become increasingly demanding due to globalization processes. This fact affects competitors to fight for better tourism products. The need for innovations in the market that can attract tourists increases and creates the competitive advantage. The most important elements that can form and develop the competitive advantage by using different skills are efficiency, quality, innovation, and satisfaction of customers' expectations. The paper is the result of the RTA scientific grant "Feasibility study of tourism product development for the Luznava Manor" programme. The aim of the paper is to explore and analyse the theoretical aspects of the competitive advantage and to identify innovations for improving the competitiveness of the Luznava Manor. The most important elements of the competitive advantage in the tourism industry have been studied, information on foods used at the beginning of the 20th century and recipes characteristic of Latvia in the period of time when the Kierbedz family lived in the Luznava Manor have been researched and summarized. It has been offered to supplement the soup assortment at the Luznava Manor with a cold salty soup ‘batvin’ or ‘holodnik’ of the authentic recipe and name, as well as a plan of communication measures to increase competitiveness has been proposed.Monographic, logical construction, scientific induction and deduction methods and a structured interview have been applied.